Lógica y semántica - Moretti, Alberto (Revista de Filosofía, 2007)
The fundamental link between logical and semantic inquiries is emphasized, and by relating some of Frege’s ideas on the concepts of logic and truth with others of Davidson’s on the Tarskian structure of interpretation, an attempt is made to clarify the Fregean point of view about the nature of the logical-semantic reflection.